CRM IMPLEMENTATION AND ITS EFFECTS ON BUSINESS PERFORMANCE, CUSTOMER RETENTION, AND PROFITABILITY: AN EMPIRICAL STUDY (International Journal of Food and Nutritional Sciences, 2021)
Customer Relationship Management (CRM) practices are business strategies designed to reduce costs and increase profitability by solidifying customer loyalty. With intense competition among insurance companies in Ghana, this study sought to assess Customer Relationship Management practices and Customer Retention in NSIA Insurance. The study was conducted to identify critical factors necessary for customer retention in carrying out customer relationship management practices in the selected insurance company and to develop effective customer relationship management practices to manage customer retention for sustainability within the insurance industry using NSIA Insurance as a case study. Well structured questionnaires and face-to-face interview were the methods adopted for the investigation of the study. A sample size of 40 respondents was considered, they were made up of customers and the staff who are fully involved in customer relationship management of the insurance company. Data collected from the completed questionnaires and the interviews were grouped into frequency tables and expressed in percentages. The researcher relied on the SPSS in interpreting the collected data. The study shows that even though NSIA insurance has policies on customer relationship management practices, these policies are not carried out fully to accomplish the ultimate goal of customer retention. The study recommends that for the insurance company to command an adequate number of loyal customers, NSIA Insurance should consistently improve on its quality of service to address the preference of the customers and consider the five service quality constructs of reliability, assurance, tangibility, empathy and responsiveness.